Menumbuhkan Minat Baca Anak: Pendampingan Pendirian Taman Baca di Madin An-Nur Desa Kedungrejo Tanjunganom Nganjuk - Suhartono; Hafidhoh, Noor; Mas'ut; Musthofa, Moh. Saiful (Ngaliman: Jurnal Pengabdian Kepada Masyarakat, 2022)
The implementation of Mentoring includes, (1) Providing Interesting Reading Materials for Children, this step is carried out in order to support the interest and visits of students at Madin An-Nur, as well as children from the Madin An-Nur environment. (2) Designing a reading garden room, this is done to increase students' interest in reading and feel at home in the reading garden for a long time. While the impact of the existing changes are (1) The existence of a reading garden at Madin An-Nur, which was initially only a place to learn basic religious knowledge, now there are additional places to foster reading interest in students, besides that there are also administrators in the reading garden. , and (2) There is an increase in reading interest in Madin An-Nur students. With the stimulus from the companion team in the form of educative activities, students/children get to know reading books and develop their reading interest. The expected outcome is to create a generation that is intellectual, a generation that likes to read and a generation that is creative.